The Buried Dog of Communist Regime : Pavel Kohout and the Possibilities of Memoires - Hanuš , Jiří (Dějiny – teorie – kritika, 2007)
Jiří Hanuš deals with „memoir-novels“ of a renowned Czech writer Pavel Kohout Z deníku kontrarevolucionáře and Kde je zakopán pes. The author attempted at depicting Kohout’s way of expression, his treatment of history and his unique contribution to the Czech literature and historiography. He analysed Kohout as a writer who describes first of all the thinking of socialist intellectuals who were actively involved in building the Communist regime in Czechoslovakia and who later ended up as „children devoured by their own revolution“. Kohout’s novels, no matter how dramatically they are built and no matter how much they witness their author’s strong ego, offer quite a few interesting insights that can be employed by contemporary historians when analysing the history of socialist utopias and socialist everyday life, but also the paradoxes of Communist power.